From milk to solid: a review and meta-regression analysis on the effects of solid feed on veal calf welfare and abomasal lesions - Cozzi, Giulio; Magrin, Luisa; Marcon, Caterina; Contiero, Barbara (Frontiers in Veterinary Science, 2025)
This study reviewed the evolution of solid feed (SF) use in veal calf nutrition and conducted a regression meta-analysis to assess its effects on abomasal health. The traditional feeding system for veal calves consisted exclusively of liquid diets based on whole cow’s milk, and more recently on formulated milk replacers. The provision of limited quantities of SF (50–250 g per calf per day) was mandated by European Union welfare regulations with the aim of improving physiological and behavioral development. Data from 13 studies published between 2000 and 2024 were analyzed to quantify the relationship between SF supply and abomasal lesions. The dataset revealed that during this time period the mean daily SF intake increased by approximately 700 g per calf. The meta-regression analysis showed a strong positive correlation between the daily dry matter of SF administered and the prevalence of abomasal damage, indicating that each additional 100 g of SF dry matter corresponded to a 4 ± 1 percentage-point increase in lesion prevalence. Starch intake, rather than neutral detergent fiber (NDF) from SF, was significantly associated with lesion occurrence (p < 0.001). These findings suggest that while the inclusion of solids improved welfare compared with milk-only diets, current high-starch feeding practices compromise gastrointestinal integrity, highlighting the need to redefine optimal SF composition and inclusion levels for sustainable and welfare-oriented veal production.